Pengaruh Gaya Kepemimpinan Kepala Desa Terhadap Motivasi Kerja Perangkat Desa di Desa Cipangeran Kecamatan Saguling Kabupaten Bandung Barat - Ramadhan; Makmur (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The following research aims to understand the leadership style of village leaders on the work motivation of village officials, as well as to analyze the impact of the leadership style of village leaders on village officials in Cipangeran, Saguling District, West Bandung Regency. The leadership style of village leaders in this study was measured through aspects of decision-making skills, motivational skills, communication skills, subordinate management skills, responsibility, and emotional control skills. Meanwhile, the work motivation of village officials was measured using internal factor indicators and external factor indicators. The research method used in this research is a descriptive and verification approach, followed by quantitative research types. The method of data collection in this research was carried out based on literature studies and field research by distributing questionnaires to the community in Cipangeran Village, Saguling District, West Bandung Regency. The results of the research show that the leadership style of the Village Head has an impact on the work motivation of village officials in Girimukti, Saguling District, West Bandung Regency. With a t-count value of 4.241> 2.086 t-table, it can be concluded that H0 is not accepted, while Ha applies. Thus, the hypothesis in this research shows that Ha is valid. Improving the leadership style of the Village Head can be done by involving village officials in decision-making, always exemplifying a disciplined work attitude towards village officials, clearly explaining tasks or jobs so that employees are able to carry out their jobs well, giving reprimands or sanctions to village officials who violate the rules, and always being wise in dealing with work problems faced by village officials. Improving the work motivation of village officials can be done by providing recognition and appreciation both verbally and in writing to employees who excel, providing compensation and bonuses to employees who excel, and providing career development paths for village officials with good work achievements.